Effect of DMSO and Its Decay Products on Spermatozoa and Survival of Loach Misgurnus fossilis L. Embryos - Kopeika, Yu. E.; Grischenko, V. I.; Kopeika, E. F.; Linnik, T. P.; Bibenko, O. V.; Zinchenko, A. A. (Problems of Cryobiology and Cryomedicine, 2002)
To examine the effect of dimethylsulfoxide (DMSO) of different purity on the genome of reproductive cells, spermatozoa from loach (Misgurnus fossilis L.) were equilibrated in 3 media containing 10 % DMSO of different purity at 4°C for 40-50 minutes. Survival of embryos derived from sperm subjected to DMSO exposure was not affected by the purity of DMSO fractions before 20‑th stage of embryo development. It was equally decreased for all three studied fractions of DMSO and it was 1/3 times lower than that in the control. It was explained by presence of cytotoxic and selective effects of DMS0 on sperm population in the ejaculate. The estimated decrease of embryo survival after 20-th stage for the embryos derived from sperm equilibrated with fraction I and II correlated with the data obtained after spectrophotometrical analysis of admixtures in DMSO solution. The decrease of embryo survival after 20-th stage was interpreted as indirect evidence of genetic disturbance caused by equilibration of sperm with fraction I and II. The equilibration of sperm with the purest (III) fraction of DMSO caused decrease of survival of embryos as well but not for all females. It was explained by less significant effect of the purest fraction of DMSO on the spermatozoa, and by variety in repair capability and genetic potential between different female individuals. The survival of embryos was dependent on the stage of development. Thus, DMSO has a cytotoxic and selective effect as well as causes some disturbance in genetic material of sperm that consequently brings to the decease of embryo survival. The estimated effect was dependent on the purity of DMSO, individual female, egg quality and stage of embryo development.